Children's Emotional Behavior in Role Playing Activities at Nadira Kindergarten, Takalar - Sri Rika Amriani; Muh. Isbar Pratama; Angri Lismayani; Fitriani Dzulfadhilah; Fitriana Fitriana (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study was to describe the Emotional Behavior of Early Childhood in Role Playing Activities at Nadira Kindergarten, Takalar Regency. This research uses a quantitative approach with a descriptive research type. The data analysis technique used in this study was quantitative using descriptive statistics, the results obtained were that there were 5 children in the 39-46 range in the good category, while 7 children in the 32-38 range were categorized as sufficient, and 4 children were categorized as lacking in range 25-31, thus it can be said that of the 16 children there were 31.25% of the children categorized as good, 43.75% of the children were categorized as sufficient, and 25% of the children were categorized as lacking, the results indicated that the child's emotional behavior had begun to develop, where it can be seen that most children are able to control their emotions, are able to be patient in waiting their turn, and are able to express their emotions while studying.